Development of a shelling method to recover whole kernels of the Cutia nut (Couepia edulis) Desenvolvimento de metódo para descorticação da castanha de Cutia em amendoas inteiras - José Dalton Cruz Pessoa; Johannes Van Leeuwen (Revista Brasileira de Fruticultura, 2006)
The kernel of the cutia nut (castanha-de-cutia, Couepia edulis (Prance) Prance) of the western Amazon, which is consumed by the local population, has traditionally been extracted from the nut with a machete, a dangerous procedure that only produces kernels cut in half. A shelling off machine prototype, which produces whole kernels without serious risks to its operator, is described and tested. The machine makes a circular cut in the central part of the fruit shell, perpendicular to its main axis. Three ways of conditioning the fruits before cutting were compared: (1) control; (2) oven drying immediately prior to cutting; (3) oven drying, followed by a 24-hour interval before cutting. The time needed to extract and separate the kernel from the endocarp and testa was measured. Treatment 3 produced the highest output: 63 kernels per hour, the highest percentage of whole kernels (90%), and the best kernel taste. Kernel extraction with treatment 3 required 50% less time than treatment 1, while treatment 2 needed 38% less time than treatment 1. The proportion of kernels attached to the testa was 93%, 47%, and 8% for treatments 1, 2, and 3, respectively, and was the main reason for extraction time differences. A amêndoa da Castanha-de-cutia (Couepia edulis (Prance) Prance), originária da Amazônia Oriental e consumida pela população local, tem sido tradicionalmente extraída do fruto com auxílio de um facão, em um procedimento perigoso, que produz somente amêndoas quebradas. Aqui é descrito um protótipo para descorticação que permite a obtenção de amêndoas inteiras sem riscos ao operador. O protótipo faz um corte circular entre as duas extremidades da casca do fruto, perpendicular ao seu eixo principal. Foi avaliado o efeito de três pré-tratamentos do fruto: (1) controle; (2) secamento em forno imediatamente antes do corte; (3) secamento em forno, seguido de um intervalo de 24 horas antes do corte. O tempo total necessário para extrair e separar a amêndoa do endocarpo e da testa foi medido. O tratamento 3 produziu os melhores resultados: 63 amêndoas por horas, sendo 90% inteiras. A extração antecedida deste tratamento requereu 50% menos tempo de extração que no tratamento 1, enquanto o tratamento 2 requereu 38% menos tempo que o tratamento1. A proporção de amêndoas aderidas à testa foi de 93%, 47% e 8% para os tratamentos 1; 2 e 3, respectivamente, e foi a principal razão da diferença entre os tempos.